Peran Ombudsman Republik Indonesia Perwakilan Provinsi Jawa Tengah dalam Penyelesaian Pengaduan Pelayanan Publik Bidang Pendidikan - Dyah Swastika; Sri Nurhari Susanto; Henny Juliani (Administrative Law Department, Faculty of Law, Universitas Diponegoro, 2022)
Abstract: The implementation of public services in the field of education is one form of the state to prosper its citizens. The implementation of these public services is one of the objects of the Ombudsman in conducting supervision. The purpose of this research is to identify and analyze the role of the RI Ombudsman Representative of Central Java Province in resolving public service complaints in the education sector. This legal writing uses an empirical juridical approach. The results of the study describe the role of the Ombudsman RI Representative of Central Java Province in resolving complaints on public services in the field of education through procedures for receiving reports on allegations of maladministration in the administration of public services in the field of education, examining the substance of the report, following up on reports within the scope of authority, compiling a Final Result Report. Examination (LAHP), recommendations, monitoring and following up on community reports with the Ombudsman Quick Response (RCO) mechanism. The Ombudsman has resolved 119 complaints, 6 of which are problems in the education sector. The obstacles faced are the lack of budget, the size of the working area, the lack of understanding of the reported agency, the reporter not having the courage to submit a complaint, and the Covid-19 pandemic. The way to overcome the obstacle is to change the strategy, provide understanding to the reporter and the reported party, and develop alternatives solution. Keywords: Role, Ombudsman, Public Service, Education Abstrak: Penyelenggaraan pelayanan publik bidang pendidikan merupakan salah satu wujud dari negara untuk mensejahterakan warganya. Penyelenggaraan pelayanan publik tersebut menjadi salah satu objek Ombudsman dalam melakukan pengawasan. Tujuan penelitan ini melakukan identifikasi dan menganalisis peran Ombudsman RI Perwakilan Provinsi Jawa Tengah dalam penyelesaian pengaduan pelayanan publik bidang pendidikan. Penulisan hukum ini menggunakan pendekatan yuridis empiris. Hasil penelitian mendeskripsikan peran Ombudsman RI Perwakilan Provinsi Jawa Tengah dalam penyelesaian pengaduan pelayanan publik bidang pendidikan melalui prosedur menerima laporan atas dugaan maladministrasi dalam penyelenggaraan pelayanan publik bidang pendidikan, melakukan pemeriksaan substansi laporan, melakukan tindak lanjut terhadap laporan dalam ruang lingkup kewenangan, menyusun Laporan Akhir Hasil Pemeriksaan (LAHP), rekomendasi, monitoring serta menindaklanjuti laporan masyarakat dengan mekanisme Respon Cepat Ombudsman (RCO). Ombudsman telah menyelesaikan pengaduan sejumlah 119 laporan, 6 diantaranya merupakan permasalahan bidang pendidikan.Kendala yang dihadapi adalah kurangnya anggaran, luasnya wilayah kerja, kurangnya pemahaman instansi terlapor, pelapor kurang berani untuk menyampaikan pengaduan, dan adanya pandemi Covid – 19. Cara yang dilakukan untuk mengatasi kendala yaitu mengubah strategi, memberikan pemahaman kepada pelapor dan terlapor, serta menyusun alternatif penyelesaian Kata Kunci : Peran, Ombudsman, Pelayanan Publik, Pendidikan